Pastoral Aspects of the Occasional Services - KIRÁLY, Lajos (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
This study examines the casualias as central to the ministry of the church from the perspective of pastoral care. At the root of the casualias is ritual, which, according to Emile Durkheim, has as its true function the strengthening and maintenance of group cohesion and solidarity, the expression of unity, the weaving of bonds between the individual and society. Pastoral psychology studies of casualias have shown that they play an important role in the community and relational experience, as communication and correlation take place between the transcendent and the human, between man and man: the individual is strengthened and experiences the welcoming, supportive, and helping presence of the community. The individual is no longer alone with his or her problems and difficulties, as he or she has a burden-relieving experience of being in contact with the community. This connection is not only embodied in words but also brought to life through non-verbal moments and ancient symbols. I will point out that providing help, according to pastoral psychology, is a communal task, which is why rituals and casualias have therapeutic and pastoral care potential.